1980
DOI: 10.1021/bi00544a006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the spontaneous transfer of phospholipids between bilayers

Abstract: A fluorescent phospholipid, 1-palmitoyl-2-pyrenedecanoylphosphatidylcholine, was used to study the mechanism of spontaneous phospholipid transfer between single-walled phospholipid vesicles. The half-time for transfer of this molecule between vesicles of dimyristoylphosphatidylcholine at 36 degrees C is 13 h if flip-flop is negligible or 24 h if flip-flop is faster than intervesicle exchange. The half-time is unaffected by the concentration of acceptor vesicles, which indicates that transfer of label takes pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(167 citation statements)
references
References 22 publications
12
155
0
Order By: Relevance
“…A plot of 1/ΔF versus (1/ΔFmax)([SUV]/[FABP]) gives a slope of 1/Kp. The partition coefficient was used to establish AOFA transfer assay conditions so as to ensure essentially unidirectional transfer [22].…”
Section: Dmentioning
confidence: 99%
“…A plot of 1/ΔF versus (1/ΔFmax)([SUV]/[FABP]) gives a slope of 1/Kp. The partition coefficient was used to establish AOFA transfer assay conditions so as to ensure essentially unidirectional transfer [22].…”
Section: Dmentioning
confidence: 99%
“…[17][18][19][20][21][22]. and with lipids bearing fluorescent dyes (e.g., [23][24][25][26][27][28][29][30]. While one might argue that inserting lipids into membranes is better achieved using soluble lipid transfer proteins.…”
Section: Ii-a Value As An Experimental Toolmentioning
confidence: 99%
“…The mechanism by which spontaneous lipid transfer occurs between membranes has been investigated in many independent laboratories [23,26,57,66,[110][111][112][113][114][132][133][134][135]. In the vast majority of cases, it has been concluded that the transfer event is a first-order process in which the rate-limiting step is desorption of lipid molecules from the donor membrane surface followed by rapid diffusion through the aqueous phase to an acceptor membrane (Fig.…”
Section: What Is the Mechanism Of Spontaneous Lipid Transfer? Iv-mentioning
confidence: 99%
See 1 more Smart Citation
“…These lipids carry a pyrenylacyl chain in either the sn-1 or sn-2 position and an unlabeled acyl chain in the other position. Similar lipids have been used by others to study either passive or protein-mediated phospholipid transfer (Charlton et al, 1978;Doody et al, 1980;Roseman & Thompson, 1980;Massey et al, 1982Massey et al, , 1984Massey et al, , 1985. By varying the position and the length of the pyrenylacyl and unlabeled acyl chain, one can systematically probe the sn-1 and sn-2 acyl binding sites of the protein.…”
mentioning
confidence: 99%